Clinical validation of Guardant360 CDx as a blood-based companion diagnostic for sotorasib. (April 2022) - Bauml, Joshua M.; Li, Bob T.; Velcheti, Vamsidhar; Govindan, Ramaswamy; Curioni-Fontecedro, Alessandra; Dooms, Christophe; Takahashi, Toshiaki; Duda, Andrew W.; Odegaard, Justin I.; Cruz-Guilloty, Fernando; Jin, Liming; Zhang, Ying; et al.
Highlights: Insufficient genotyping remains common in non–small-cell lung cancer (NSCLC). Comprehensive genotyping is critical for proper management of NSCLC patients. Guardant360 CDx is a next-generation sequencing–based liquid biopsy test. Guardant360 CDx has clinical validity in identifying KRAS p.G12C–mutant NSCLC. Guardant 360 CDx may be a useful tool for determining eligibility of sotorasib therapy. Abstract: Objectives: Effective therapy for non–small-cell lung cancer (NSCLC) depends on morphological and genomic classification, with comprehensive screening for guideline-recommended biomarkers critical to guide treatment. Companion diagnostics, which provide robust genotyping results, represent an important component of personalized oncology. We evaluated the clinical validity of Guardant360 CDx as a companion diagnostic for sotorasib for detection of KRAS p.G12C, an important oncogenic NSCLC driver mutation. Materials and Methods: KRAS p.G12C was tested in NSCLC patients from CodeBreaK100 (NCT03600833) in pretreatment plasma samples using Guardant360 CDx liquid biopsy and archival tissue samples using therascreen® KRAS RGQ polymerase chain reaction (PCR) kit tissue testing. Matched tissue and plasma samples were procured from other clinical trials or commercial vendors, and results were compared. Demographics and clinical characteristics and objective response rate (ORR) were evaluated. Results: Of 126 CodeBreaK patients, 112 (88.9%) were tested for KRAS  p.G12C mutations with Guardant360 CDx. Among 189 patients in the extended analysis cohort, the positive and negative percent agreement (95% CI) for Guardant360 CDx plasma testing relative to therascreen® KRAS RGQ PCR kit tissue testing were 0.71 (0.62, 0.79) and 1.00 (0.95, 1.00), respectively; overall percent agreement (95% CI) was 0.82 (0.76, 0.87). TP53 co-mutations were the most common regardless of KRAS p.G12C status ( KRAS p.G12C–positive, 53.4%; KRAS p.G12C–negative, 45.5%). STK11 was co-mutated in 26.1% of KRAS p.G12C–positive samples. The ORR was similar among patients selected by plasma and tissue testing. Conclusion: Comprehensive genotyping for all therapeutic targets including KRAS p.G12C is critical for management of NSCLC. Liquid biopsy using Guardant360 CDx has clinical validity for identification of patients with KRAS  p.G12C–mutant NSCLC and, augmented by tissue testing methodologies as outlined on the approved product label, will identify patients for treatment with sotorasib.